Identifying of Anti-Thrombin Active Components From Curcumae Rhizoma by Affinity-Ultrafiltration Coupled With UPLC-Q-Exactive Orbitrap/MS - Lan, Zhenwei; Zhang, Ying; Sun, Yue; Wang, Lvhong; Huang, Yuting; Cao, Hui; Wang, Shumei; Meng, Jiang (Frontiers in Pharmacology, 2021)
In modern studies concerning products originated from natural plants, clarifying the active ingredients that actually bear a certain function is of great help in both explaining their mechanisms of the function and in quality control of their production. As a traditional functional plant, Curcumae Rhizoma (CR), in its long-term usage, has been proved to effective in promoting blood circulation and removing blood stasis. However, the components that really play a role in its huge compound library are still unclear. Our work is to develop a high-throughput screening method to identify thrombin inhibitors in CR, and validate them by in vitro and in vivo experiments. The effect of CR on thrombin in HUVECs cells was determined by ELISA, then, an affinity-ultrafiltration-UPLC-Q-Exactive Orbitrap/MS approach was applied. Agatroban and adenosine were used as positive and negative drugs respectively to verify the reliability of the established method. The in vitro activity of the compounds was determined by specific substrate S-2238. The in vivo effect of the active ingredients was determined using zebrafish. Molecular docking was used to understand the internal interactions between compounds and enzymes. ELISA results showed that CR had inhibitory effect on thrombin. The screening method established in this paper is reliable, by which a total of 15 active compounds were successfully identified. C7, 8 and 11 were found to bear an in vitro thrombin-inhibitory activity, and be able to significantly inhibit the thrombosis in zebrafish models at a safe dose, which is firstly reported worldwide. Molecular docking studies were employed to analyze the possible active binding sites, with the results suggesting compound 16 as a probably better thrombin inhibitor as compared with the other compounds. Based on the affinity-ultrafiltration-UPLC-Q-Exactive Orbitrap/MS approach, a precisely targeted therapy method using bio-active compounds from CR might be successfully established, which also provides a valuable reference for targeted therapy, mechanism exploration and quality control of traditional herbal medicine.